Internal and Combination Resonances in a Kinematically Excited System of Non-Prismatic Rods - Foryś, A.; Foryś, A.S. (Engineering Transactions, 1995)
Internal and periodic combination resonances in a system of three coupled non-prismatic rods with articulated joints are analyzed. The resonances are of a parametric nature. The transverse vibrating system is placed on the vertically moving support. In the equation of motion two kinds of nonlinearities of geometrical nature appear. The considered problems may have a practical significance for the paraseismic phenomena when the weak excitation may cause great effects because of the autoparametric resonances.